PENGARUH PENGUMUMAN PEMBAGIAN DIVIDEN TERHADAP HARGA SAHAM SEBELUM DAN SESUDAH EX DIVIDEND DATE PADA KELOMPOK INDUSTRI MANUFAKTUR DAN JASA YANG TERDAFTAR DI BEI (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2017)
Based on the theory Efficiency Market Hypothesis, stock prices will react to theinformation which the reaction took place in the days around the date exdividendwhich is the date when the right to dividend for the year is released from its stake Byusing different test research proposes, see sajauh where the effect of theannouncement of dividend distribution to the stock price before and after the exdividenddate, especially for groups of manufacturing industry and service industry.Based on the background, theoretical basis, data analysis and hypothesis testingresults, it can be concluded in which the differences are stock prices before andafter the ex-dividend date on manufacturing companies. There are differences instock prices before and after the ex-dividend date on the group service companyspecialized corporate banking services, which means the average stock price beforethe ex-dividend date is greater than the average stock price after the ex-dividenddate, so it can be said to be the mean average stock price decline in the ex-dividenddate. Based on these results the first and second hypothesis in this study received.